Notes on Early Land Plants Today. 26. Miscellaneous synonyms in liverworts (Marchantiophyta) - Gradstein, S Robbert (Phytotaxa, 2013)
Aneura bipinnata (≡ Riccardia bipinnata, described from Jamaica as Jungermannia bipinnata (“2-pinnata“) by Olof Swartz (1788, 1806), is one of the oldest names in Aneuraceae and one of the poorest known. Swartz’ original description and the brief diagnosis in Synopsis Hepaticarum (Gottsche et al. 1846) are the only available descriptions for the species. Stephani (1899) was unable to locate material of Aneura bipinnata and listed the species without description in his Species Hepaticarum. Swartz (1806) compared his Jungermannia bipinnata with Jungermannia multifida (≡ Riccardia multifida), a widespread Holarctic species. My study of the holotype material of Jungermannia bipinnata kept in S revealed that the species is identical to R. multifidaand a synonym of the latter. Characteristic are the creeping to somewhat procumbent, several cm long shoots with regularly 2(-3)-pinnate branching, the linear, broadly winged branches and the swollen, biconvex main axis with or without a narrow wing.